Promoting youth engagement in agriculture through land titling programs: evidence from Tanzania - Msangi, H.A.; Waized, B.; Ndyetabula, D.W.; Manyong, V. (Elsevier, 2024)
In many African countries, land access and tenure insecurity pose significant challenges to agriculture, in particular for the youth. As the farming population ages, young people are expected to take over, but they don't often show much interest in farming, which could harm the future of agriculture in Africa, where the population is the youngest. Land reforms and titling programs are suggested as amongst strategies to make agriculture more attractive to investors and promote youth involvement. As a result, majority African countries undertook reforms such as land titling, ownership mapping and market facilitation as policy prescriptions for promoting youth involvement in agriculture. Nonetheless, the impact of these programs is not well documented in the body of literature thus constraining policy decisions. This study examines the impact of land titling on youth participation in agriculture in Tanzania, using 2020/2021's wave of Tanzania national panel survey data with a sample size of 2725 youth households from 419 enumeration areas. The study finds that land titling is a critical factor in promoting youth participation in agriculture in Tanzania, with young people who have titled land tending to allocate more resources (time) to farming activities. The study also identified farm size, educational level, and land dispute experience as significant factors influencing youth participation in agriculture. Based on these findings, the study recommends interventions to promote youth participation in agriculture in Tanzania, including investing in land titling programs that specifically target young people and promoting educational programs that equip young people with foundational skills. The study also highlights the need for tailored interventions that address the specific needs of different groups of young people. Overall, the study underlines the importance of promoting youth participation in agriculture in Tanzania and by extension to other African countries to contribute to food security and rural development.